(untitled) (Jagannath University Journal of Arts, 2026)
In this research titled "Rabindranath’s Songs of the ’Puja’ Phase: The Presence of the Divine and Nature," we explore how the themes of divinity and nature are interwoven within the devotional songs composed by the eminent Bengali musician and poet Rabindranath Tagore. We examine how Rabindranath employed elements of nature to express his spiritual thoughts. How did he use various natural settings and phenomena in his devotional songs? Often, nature and the divine appear to merge into one essence. At other times, nature plays an inevitable and essential role in conveying a divine experience. To undertake this study, we have selected a number of songs from Rabindranath’s Puja (worship) phase. Using textual analysis, comparative methods, and descriptive approaches, we observe that in these devotional compositions, God is undoubtedly present, but nature, too, emerges as a vital and recurring theme—often indispensable. These songs transform Rabindra Sangeet—particularly his devotional pieces—into a profound medium of spiritual and aesthetic realization, where the sacred and the sensory beautifully converge. Jagannath University Journal of Arts, v-15, i-01, 2025:p91-100